Concept. Linguvopragmatic Analysis Of Religious Concepts - Gulshoda O‘tkirbek qizi Pratova (Genius Journals, 2022)
This article focuses on the cognitive analysis of “religious” concepts and the linguocultural aspects of the various means by which the semantic field is represented. The problem is solved with some examples and theoretical data.
Keywords: Knowledge; cognitive; linguocultural; conceptual